The background of the Gospels : Judaism in the period between the Old and New Testaments - Fairweather, William (Bloomsbury Academic collections., 2015)
Covering the period from the Maccabean revolt to the destruction of Jerusalem under Titus, Fairweather's impressive work should be an important point of reference for those wanting to develop their knowledge on the evolution of Judaism as a spiritual movement.